Smoking stone - Ijäs, Petro ([Vihti] : MUN-Records, 2015)
9 kappaletta.
Adrenalin ; Wonderland ; Great blue sky ; Birds ; Early morning hours ; Free ride ; Industrially bored ; Something about being sad ; Outside.
Petro Ijäs (tuottaja).
Petro Ijäs (kitarat, sähköbasso, lauluääni, rummut, kosketinsoittimet, muut soittimet).
Keywords: Ijäs, Petro -- albumit; rock; indierock; progressiivinen rock